PENGUJIAN INOKULAN KONSORSIUM DEKOMPOSER BERAGEN HAYATI DALAM LAJU DEKOMPOSISI JERAMI SELAMA MASA INKUBASI YANG DILAKUKAN DI RUMAH KACA - Turmuktini, Tien; Simarmata, Tualar; Natalie, Betty; Hersanti, Hersanti; Yuwariah, Yuyun (CEFARS : JURNAL AGRIBISNIS DAN PENGEMBANGAN WILAYAH, 2011)
The use of fresh straw directly on agricultural land turns out have a negarif impact, among others, is the danger of grems contamination on the straw from theprevious crop and environmental pollution due to the formation of methane resulted from anaerobic decomposition of flooded rice field. The recommended solution is composting straw earlier. The main obstacle of this straw composting include necessary labor (preparation of materials, transportation, maintenance) and the cost is relatively high. An alternative solution is to do straw inoculation with bio agent consortium decomposers before tillage (direct composting). Inoculation consortium decomposer is added to the straw need to be tested its effect on decomposition rate, especially incubation time and incorporation also the type of consortium. The aim of this research is to determine the bio agent inoculant consortium decomposer incubation time to accelerate straw decomposition and nutrient availability. The experiments was conducted in the greenhouse of the Faculty of Agriculture University of Padjadjaran in April to May 2010, using a randomized block design in factorial pattern repeated three times, as factor I: Incubation time (1, 2, 3 and 4 MST) and factor II: inoculant: no inoculants; formula A = inoculant decomposers (Bacillus sp, Cytophaga sp, Streptomyces sp) and formula B = inoculant decomposers (Bacillus sp, Cytophaga sp, T. harzianum). The results of this experiment showed that administration of a consortium of formula A and B can accelerate the decomposition of straw (temperature increases and pH decreases), and with increasing incubation time can increase the value of C-organic, N-total, decrease C/N compared to controls.